On a collection of stomatopod Crustacea in the Fishery Survey of India, research cruises from the northeast coast of India - Silambarasan, Krishnan; Kar, A.b.; Prasad, G.v.a.; Pattnayak, S.k.; Jeyabaskaran, R. (Zootaxa, 2025)
The stomatopod fauna in Indian waters is relatively well documented, with 76 species recorded to date. This report is based on collections from exploratory fishery resources surveys conducted by the Fishery Survey of India during research cruises from 2019 to 2020. A total of 14 species were recorded during these surveys along the northeast coast of India. Among these, four species are reported as new records for the region: Clorida bombayensis (Chhapgar & Sane 1967), Carinosquilla lirata (Kemp & Chopra, 1921), Lophosquilla tiwarii Blumstein, 1974 and Squilloides leptosquilla (Brooks, 1886).